Pengaruh Pengetahuan tentang ASI Eksklusif dan Makanan Pendamping ASI Dini dengan Kejadian Stunting di Puskesmas X - Maria Fatima Bara; Tuti Asrianti Utami; Wilhelmus Hary Susilo (Universitas Malahayati Lampung, 2025)
ABSTRACT Stunting is a measure obtained on a child's nutritional status based on his height which is determined by the comparison of the heights of children of his age. Factors causing stunting are mothers' lack of knowledge about the importance of exclusive breastfeeding and the providing of early weaning foods. This study aims to analyze the influence of mothers' knowledge about the importance of exclusive breastfeeding and early weaning food feeding on the incidence of stunting at the X District Health Center, West Jakarta. This research is a quantitative study with a logistic regression model using a cross-sectional approach. The data collection method used was distributing questionnaires. The sampling technique in this research used purposive sampling with 71 respondents. The results of the univariate analysis showed that 48 (67.6%) respondents had less knowledge about giving exclusive breastfeeding, 45 (63.4%) had less knowledge about providing weaning foods, 23 (32.4%) had stunted toddlers in the short category (stunted) and stunted toddlers in the very short category (severely stunted) were 31 (43.7%).The results of the mann-whitney analysis test with the condition that it is significant if the p-value 0.05 shows that there is a significant influence between knowledge about exclusive breastfeeding with the incidence of stunting (p-value = 0.002) and knowledge about the providing of providing early weaning foods with the incidence of stunting (p-value = 0.001). Keywords: Stunting, Exclusive Breastfeeding, Weaning Foods ABSTRAK Stunting merupakan ukuran yang didapatkan pada status gizi anak berdasarkan tinggi badannya yang ditentukan oleh perbandingan tinggi pada anak-anak seusianya. Faktor penyebab terjadinya stunting adalah kurangnya pengetahuan ibu tentang pentingnya pemberian ASI eksklusif dan pemberian makanan pendamping ASI dini. Penelitian ini bertujuan untuk menganalisis pengaruh pengetahuan ibu tentang pentingnya pemberian ASI eksklusif dan makanan pendamping ASI dini dengan kejadian stunting di Puskesmas X Jakarta Barat. Penelitian ini merupakan penelitian kuantitatif dengan model non-parametric test dengan menggunakan uji mann-whitney menggunakan pendekatan cross sectional. Metode pengumpulan data yang digunakan berupa penyebaran kuesioner. Teknik pengambilan sampel dalam penelitian ini menggunakan purposive sampling dengan responden sebanyak 71 responden. Hasil analisis univariat menunjukan responden yang mempunyai pengetahuan kurang tentang pemberian ASI eksklusif sebanyak 48 (67,6%), pengetahuan kurang tentang pemberian MP ASI sebanyak 45 (63,4%), balita stunting kategori pendek (stunted) sebanyak 23 (32,4%), dan balita stunting dengan kategori sangat pendek (severely stunted) sebanyak 31(43,7%). Hasil analisis uji mann-whitney dengan ketentuan bermakna jika p value 0,05 menunjukan adanya pengaruh yang signifikan antara pengetahuan tentang ASI eksklusif dengan kejadian stunting (p value=0,002), dan pengetahuan tentang pemberian MP ASI dini dengan kejadian stunting (p value=0,001). Kata Kunci: Stunting, ASI Eksklusif, Makanan Pendamping ASI